When the clock Is ticking: the role of mitotic duration in cell fate determination - Sala, Cornelia; Schiebel, Elmar (Bioessays, 2025)
Mitosis is a crucial phase of the cell cycle, during which several mechanisms work together to ensure accurate chromosome segregation and to eliminate defective cells if errors occur. One key mechanism is the spindle assembly checkpoint (SAC), which upon mitotic errors—such as those induced by genetic mutations, drug treatments, or environmental stresses—arrest cells in mitosis. Arrested cells may undergo apoptosis during mitosis or eventually exit mitosis even if the damage remains unrepaired. Mitotic exit is driven by a reduction in cyclin B1 levels, regulated during mitosis by multiple mechanisms affecting both its synthesis and degradation. Strikingly, cells harboring the tumor suppressor p53 can monitor the duration of mitosis and encode this information as a form of “mitotic memory”. This memory influences the fate of daughter cells after mitotic exit by inducing G1 arrest through p53-dependent expression of the cyclin-dependent kinase (CDK) inhibitor p21. Recent studies have proposed mechanisms by which cyclin B1 levels are regulated during mitotic arrest and how p53 promotes mitotic-arrest-dependent transcription of p21 in G1. These findings indicate that both the expression of regulators that control mitotic duration and the activity of proteins that monitor the duration of mitosis and halt proliferation work together to determine cell fate following mitotic errors. Understanding these mechanisms offers valuable insights for cancer therapy, particularly regarding the strategic application of antimitotic agents.